Danantara and the Reform of Indonesia's Economy: A Multi-Dimensional Literature Review on Investment, SOEs, and National Development - Chandra, William; Silalahi, Wilma (APPS Publications, 2024)
Danantara, Indonesia’s newly established sovereign wealth fund (SWF), holds transformative potential for economic reform. This article analyzes Danantara’s strategic role in optimizing investment management, enhancing the performance of State-Owned Enterprises (SOEs), and advancing Indonesia’s national development agenda. Employing a qualitative literature review of peer-reviewed sources and comparative SWF case studies (primarily Norway and Singapore), the study highlights that Danantara can reduce inefficiencies in SOE capital allocation, strengthen domestic investment capacity, and lower reliance on foreign debt. Danantara’s structure mirrors successful international SWF models while adapting to Indonesia’s legal and institutional context. However, persistent risks such as political interference and governance gaps may hinder its long-term success. This literature-based approach allows a broad yet integrative view but is limited by the absence of empirical validation or field data. Strengthening legal safeguards and aligning SOE mandates with national industrial strategy emerge as critical steps toward Danantara’s effective implementation.